Responding to the critics: Implementation of TBLT in Japan - Harris, Justin (Universitas Pendidikan Indonesia, 2018)
This paper outlines a qualitative study of 10 in-service teachers in Japan who use a task-based language teaching (TBLT) approach in their language classrooms. The study investigates the reasons why these teachers began using TBLT, their beliefs about the advantages and disadvantages of implementing TBLT, and whether or not they agree with common criticisms levelled at TBLT for use in foreign language classrooms in Japan and Asia in general. Critics argue that TBLT is not suitable for many language learning situations, explaining that students are used to more ‘traditional’ teacher-centered language classes and that they prefer more ‘passive’ approaches. Such criticisms also hold that TBLT is not able to adequately prepare students for the high-stakes tests that are used for secondary school and university entrance purposes. The results from interviews with these 10 teachers suggest that they reject many of these criticisms, and are in fact successfully using TBLT to develop both language ability and motivation in their students. At the same time, the teachers noted that there may be a need to use a ‘weaker’ form of TBLT with beginner students, or with those used to more passive styles of learning. They also highlighted the importance of heavily scaffolding tasks in such cases. Finally, a number of the teachers discussed the need for the development of more TBLT related materials, both for students and teachers.